Individual income, incomplete information, and aggregate consumption - Jörn-Steffen Pischke (Zentrum für Europäische Wirtschaftsforschung (ZEW); ZBW – Leibniz Information Centre for Economics, 1991)
In this paper I study a model of life-cycle consumption in which individuals react optimally to their own income process but ignore economy wide information. Since individual income is less persistent than aggregate income consumers will react too little to aggregate income variation. Aggregate consumption will be excessively smooth. Since aggregate information is slowly incorporated into consumption, aggregate consumption will be autocorrelated and correlated with lagged income. The second part of the paper provides empirical evidence on individual and aggregate income processes and calibrates the model using the estimated parameters. The mode predictions roughly correspond to the empirical findings for aggregate consumption data. Allowing for the existence of measurement error in micro income, durables, finite lifetimes of consumers, and advance information improves the predictions of the model.
Keywords: E21; 330